2001
DOI: 10.2355/isijinternational.41.1010
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Oxidation Behavior of Low Pressure Plasma Sprayed Iron Aluminides.

Abstract: Microstructure and oxidation behavior of plasma sprayed iron aluminide have been investigated focusing on the spraying conditions of atmosphere and pressure. Iron aluminide powder for spraying was prepared by ball milling of turnings fabricated from an Fe-40at%Al ingot. Microstructure of laminated layers including cavities was observed in all samples and particles with a size of about 100 mm were observed only in the sample sprayed in 50 Torr Ar atmosphere. Chemical analysis revealed an amount of aluminium los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Refs. [6,19,22,26,27]. Unfortunately, the occurrence of dierent polytypes of Al 2 O 3 at higher temperatures or in dierent environments makes it dicult to extrapolate the results obtained at higher temperatures to the experiments performed in this work.…”
Section: Al2o3 Fe2o3mentioning
confidence: 54%
“…Refs. [6,19,22,26,27]. Unfortunately, the occurrence of dierent polytypes of Al 2 O 3 at higher temperatures or in dierent environments makes it dicult to extrapolate the results obtained at higher temperatures to the experiments performed in this work.…”
Section: Al2o3 Fe2o3mentioning
confidence: 54%
“…In this respect, the PTA technique is uniquely suitable compared to other thermal spray techniques, because the PTA torch is designed to offer a heat flux towards the substrate high enough for the substrate surface to melt. In other thermal spray coating processes, such as arc spray [21], low pressure plasma spray [22], air plasma spray [23] and high velocity oxyfuel (HVOF) spray [24][25][26][27][28], the torches are designed to operate with a "cold" (in comparison to the melting point of the substrate) substrate surface and thus no surface melting can occur. It is interesting to note that the dilution from the substrate, which is inevitable in the PTA process and usually regarded as a disadvantage in comparison with other thermal spray techniques, is a pre-requisite for an in-situ reaction coating process to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…Many thermal spray coating techniques, such as arc spray [21], low pressure plasma spray [22], air plasma spray [23] and high velocity oxyfuel (HVOF) spray [24][25][26][27][28], have been explored for depositing thick aluminide coatings on various steel substrates, with aluminide powder as the feeding materials. Among the above processes, the HVOF process is most attractive because the high velocity of sprayed and melted powders in this process produces coatings with higher density and better bonding to substrates than the coatings obtained with conventional thermal spray processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through modification techniques such as pre-heating and post-weld heating, crack-free iron aluminide layers could be deposited and outstanding sulfidation resistance was achieved [24]. Masahashi et al [25] applied a low-pressure plasma spray technique to deposit iron aluminide on pure iron substrate. They revealed that the existence of non-melting particles in the iron aluminide layer is beneficial for oxidation resistance, because aluminium volatilization and impurity contamination is suppressed in the non-melting particle deposition.…”
Section: Introductionmentioning
confidence: 99%